PENDAMPINGAN DAN PENERAPAN MEDIA SOSIAL INSTAGRAM UNTUK PENINGKATAN PRODUKTIVITAS USAHA SEROKAN SAMPAH - Riyan Gunawan; M. Islam Mahdi (Jurnal PkM Pemberdayaan Masyarakat, 2020)
Competition in the world of the distribution industry is getting tougher. One of the things that makes distribution companies able to survive is the provision of timely products for consumers at the right time, and at an economical cost. The availability of products and the economical selling price can only occur if there is good coordination between the company and the parties in its supply chain. Micro-medium enterprises are part of the national business. MSMEs can also be considered locomotives of national and regional economic growth (regions) because it has the potential to empower all existing resources and encourage the growth of entrepreneurial development. The role of MSMEs in Indonesia is to increase employment opportunities, equalization of income, rural economic development, increase non-oil and gas exports, and contribute to the increase in GDP. On this basis, STMIK Pringsewu works with Pekon Tambahrejo to provide mentoring services for people who have a home industry business to have a digital-based sales platform that is social media. This activity aims to provide understanding for MSME actors on how to market food products, crafts, clothing, services, and others using social media. From this activity, the people of Pekon Tambahrejo who have a home industry business can market products quickly, precisely, and safely so that businesses can provide comfort for customers.